A indisciplina no interior da escola: uma aproximação com o outro - Bortolás, Sílvia (2002)
This paper aims to show how students become, or were turned into, undisciplined by speeches and practices. It was developed among a Fifth Grade teenagers group composed by failed students of a public school in Santa Maria-RS. This project intends to describe how undisciplined students were seen and treated. What were their knacks? In which way did the discipline and its methods, such as notebooks and students’ personal files, work? What was this school daily routine? The research in this school is justified by the need of a reflection about the production of subjectivity inside a public school from its practices, speeches and silences. Considering this, culture shows us a scholar community’s uses, and customs. Sometimes, this culture may bring divergences, because it faces ethic and moral values. However, through dialogue, can also provide union. Due to this, culture will de described for ethnographic research methods: pictures, document analysis, informal chats, interviews, observation. It slants to the Cultural Studies when related to the subjectivity production of undisciplined students’ delinquent culture. Authors as Michael Foucault, Michael de Certeau, Mariza Eizirik, Peter Mclaren, Paulo Freire, among others, are related in this paper for their contributions and studies which guided me to stand for resistance as possibility of recreate another space with new experiences.